Protocol for a prospective randomized controlled trial of recipient remote ischaemic preconditioning in orthotopic liver transplantation (RIPCOLT trial). Issue 1 (December 2016) - Robertson, Francis; Goswami, Rup; Wright, Graham; Fuller, Barry; Davidson, Brian
Abstract Ischaemic reperfusion (IR) injury is a major cause of graft loss, morbidity and mortality following orthotopic liver transplantation (OLT). Demand for liver transplantation has resulted in increasing use of marginal grafts that are more prone to IR injury. Remote ischaemic preconditioning (RIPC) reduces IR injury in experimental models, but recipient RIPC has not been evaluated clinically. Methods A single-centre double-blind randomized controlled trial (RCT) is planned to test the hypothesis that recipient RIPC will reduce IR injury. RIPC will be performed following recipient anaesthetic induction but prior to skin incision. The protocol involves 3 cycles of 5 min of lower limb occlusion with a pneumatic tourniquet inflated to 200 mmHg alternating with 5 min of reperfusion. In the control group, the sham will involve the cuff being placed on the thigh but without being inflated. The primary endpoint is ability to recruit patients to the trial and safety of RIPC. The key secondary endpoint is a reduction in serum aspartate transferase levels on the third post-operative day. Discussion RIPC is a promising strategy to reduce IR injury in liver transplant recipients as there is a clear experimental basis, and the intervention is both inexpensive and easy to perform. This is the first trial to investigate RIPC in liver transplant recipients. Trial registration Clinicaltrials.govNCT00796588